2018
DOI: 10.2134/jeq2017.03.0124
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Road Salt in Private Drinking Water Wells in a Southeastern New York Suburban Township

Abstract: We used a GIS analysis of sodium and chloride concentrations in private water wells in a southeastern New York township to describe the pattern of distribution of road salt in aquifers tapped for drinking water. The primary source of road salt was sodium chloride, and sodium and chloride concentrations were significantly correlated ( = 0.80, < 0.01). Chloride concentrations in wells increased as the percentage of impervious surface cover (ISC) within a 250-m radius around wells increased ( = 0.87, < 0.01) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 28 publications
2
31
0
Order By: Relevance
“…Increasing Na þ concentrations are caused by the combination of road salts, water softeners, irrigation waters, fracking brines and sewage inputs (e.g. [27,32,34]). Many countries outside of North America and certain regions of Europe have little snow and do not rely on road salts.…”
Section: (A) Freshwater Salinization Syndrome Mobilizes Mixtures Of Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing Na þ concentrations are caused by the combination of road salts, water softeners, irrigation waters, fracking brines and sewage inputs (e.g. [27,32,34]). Many countries outside of North America and certain regions of Europe have little snow and do not rely on road salts.…”
Section: (A) Freshwater Salinization Syndrome Mobilizes Mixtures Of Mmentioning
confidence: 99%
“…However, chemical mixtures enriched in Na þ may be a surrogate for other anthropogenic activities related to sewage inputs, water softeners or irrigation (e.g. [27,34]). Tracing and quantifying relative contributions of Na þ ions from different non-point sources in watersheds warrants further study.…”
Section: (A) Freshwater Salinization Syndrome Mobilizes Mixtures Of Mmentioning
confidence: 99%
“…B 374: 20180019 of North America, 25 to 50% of applied road salts enter groundwater, leading to groundwater chloride concentrations as high as 2800 mg l 21 [50,51]. For example, in southern New York (USA), more than 50% of wells used for drinking surpassed the United States (US) Environmental Protection Agency secondary drinking water recommendation of 250 mg Cl 2 l 21 [52]. Furthermore, fixing road-salt contaminated water supplies in two towns in New York (USA) cost $4.7 million (20 homes) and $13.2 million (500 homes), respectively [53].…”
Section: Consequences Of Salinizationmentioning
confidence: 99%
“…As salinization of freshwater ecosystems resulting from deicing and anti-icing salts continues, the regulatory and management challenge for winter road maintenance programmes will be to balance the need to protect public safety and reduce the economic costs of winter storms with the need to protect environmental health and infrastructure integrity related to excess salt, and to address potential drinking water/public health related to increased dietary intake of sodium [4,21,115,116]. Our study found low temperature can reduce the frequency or intensity of salt-related toxic events expected based on winter de-icing activities that increase NaCl concentrations.…”
Section: (C) Regulatory and Management Implications Of The Relationshmentioning
confidence: 99%